Comparison of beta binomial and other methods for estimation of heritability of stayability for unbalanced data - PAUL, AMRIT KUMAR; BHATIA, V K (The Indian Journal of Animal Sciences, 2014)
Stayability being a binary trait in animal breeding needs thorough genetic analysis. The procedure of beta-binomial is modified and used in unbalanced data set, Dempster-Lerner method was also used to estimate the heritability of stay ability, and was subsequently compared empirically with the beta-binomial method. For all these comparisons the situation of unbalanced data was considered. The unbalancedness led to estimates with large standard error. Further relative root mean square error was also obtained and found that precision and accuracy of estimates were affected by unbalancedness. The results of beta-binomial method and Dempster-Lerner method of estimation are almost similar.